Effect of alternative photostimulable phosphor plates erasing times on subjective digital image quality - Melo, D. P.; Pontual, A. dos Anjos; de Almeida, S. M.; Campos, P. S. F.; Alves, M. C.; Tosoni, Guilherme Monteiro [UNESP] (British Inst Radiology, 2010)
Objective: To evaluate the influence of alternative erasing times of DenOptix (R) (Dentsply/Gendex, Chicargo, IL) digital plates oil subjective image quality and the probability of double exposure image not Occurring.Methods: Human teeth were X-rayed with phosphor plates using tell different erasing times. Two observers evaluated the images for subjective Image quality (sharpness, brightness, contrast, enamel definition, dentin definition and dentin-enamal Junction definition) and for the presence or absence of double exposure image. Spearman's correlation analysis and ANOVA was performed to verify the existence ora linear association between the subjective image quality parameters and the alternative erasing times. A contingency table was constructed to evaluate the agreement among the observers, and a binominal logistic regression was performed to verify the correlation between the erasing time and the probability of double exposure image not occurring.Results: All 6 parameters or image quality were rated high by the examiners for the erasing times between 25 s and 130 s. The same erasing time range, from 25 to 130 s, was considered a safe erasing time interval, with no probability of a double exposure image Occurring.Conclusions: The alternative erasing times from 25 s to 130 s showed high quality and no probability of double image Occurrence. Thus, it is possible to reduce the operating time or the DenOptix (R) digital system Without jeopardizing the diagnostic task.Dentomaxillofacial Radiology (2010) 39, 23-27. doi: 10.1259/dmfr/49065239.
Keywords: dental radiography; digital imaging; density; contrast